The Role of Vitamin D Supplementation in Cystic Fibrosis: A Systematic Review - M Asadi; A Najarzadeh; A Rajizadeh (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2016)
Cystic fibrosis (CF) is the most common genetic respiratory disease in the west, which is due to a malfunction in protein of cystic fibrosis transmembrane regulator (CFTR). Since some studies showed the effect of vitamin D supplementation and increment in 25OHD serum level in these patients, this study aimed to conduct a review in this scope. For reaching the available studies, a search was conducted on the studies published between2009 to 2014 in English language with the key words of vitamin D deficiency, 25OHD serum level, vitamin D supplementation and relationship with cystic fibrosis in PubMed and Google Scholar databases. In Most studies conducted on the effect of vitamin D supplementation on 25OHD serum level, an increment in 25OHD serum level was observed, though it did not reach the therapeutic target level (> 75 nmol / l or> 30 ng / ml). As a matter of fact, few studies reached the therapeutic targets. Therefore, supplementation with vitamin D in patients with CF may assist to increase the level of serum 25OHD, though achieving appropriate levels of serum 25OHD depends on conducting more studies.